Understanding generational and perceptual differences in ethical behavior : growing old is not the same as growing up! - Poulose, Jeanne, (SAGE Business cases., 2024)
The Curriculum Development Committee, usually responsible for the task of developing new courses and programs and tweaking existing ones, had turned into a debating arena, with several attendees accusing the younger generation of indulging in unethical practices at the workplace. The younger members, in turn, accused the older generation of being rigid and resistant to change, possessing inflated egos and a very narrow mindset. Professor T. Rajagopalacharya, director of the SC Business School, wanted to put an end to this debate because he believed that the disagreements generated over time among faculty members, due to the generation gap, were at the root of such toxic prejudices and stereotypes. But he also knew that because collaboration between generations was crucial, it was important to clear the air. To do this, however, he knew that he had to present facts. Considering the difficulty in measuring ethics, he brought together a team of experienced and skilled professors to explore the perception of ethical standards among various generations and present the findings within a stipulated time. The study findings would help answer the question of whether there was a difference in the ethical behaviors at the workplace among employees of different generations. It would help Professor Rajagopalacharya develop the appropriate workplace interventions to reduce the intergenerational conflict. Using the facts in the case, students will be asked to describe the cause of the rising generational differences. The interpersonal conflict arising from perceptual differences among employees of different generations can be explored using concepts such as values and approaches to work, diversity and inclusion, perceptual interpretation errors, and judgmental errors in organizational behavior. Students will gain practice applying statistical tools such as analysis of variance (ANOVA) and analysis of covariance (ANCOVA) to end the debate between the younger and older generation